2023
DOI: 10.1088/1674-1056/ad0144
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring OAM spectrum of high-order harmonic generation driven by two mixed Laguerre–Gaussian beams with nonzero radial nodes

Beiyu 倍羽 Wang 汪,
Jiaxin 嘉鑫 Han 韩,
Cheng 成 Jin 金

Abstract: The extreme ultraviolet (XUV) light beam carrying orbital angular momentum (OAM) can be produced via high-order harmonic generation (HHG) due to the interaction of an intense vortex infrared laser and a gas medium. Here we show that the OAM spectrum of vortex HHG can be readily tailored by varying the radial node (from 0 to 2) in the driving laser consisting of two mixed Laguerre-Gaussian (LG) beams. We find that due to the change of spatial profile of HHG, the distribution range of OAM spectrum can be broaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…[22][23][24][25][26] The HHG process has also been studied extensively in theory and experiment for generating XUV vortices, which has emerged as an important research area. [27][28][29][30][31][32][33] Researchers have made significant progress in understanding and manipulating XUV vortex beams generated through the HHG process. Zürch et al experimentally found that the phase singularity of vortex properties of the driving beam can be transferred into the HHG.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The HHG process has also been studied extensively in theory and experiment for generating XUV vortices, which has emerged as an important research area. [27][28][29][30][31][32][33] Researchers have made significant progress in understanding and manipulating XUV vortex beams generated through the HHG process. Zürch et al experimentally found that the phase singularity of vortex properties of the driving beam can be transferred into the HHG.…”
Section: Introductionmentioning
confidence: 99%